Clinical characteristics of respiratory tract infection caused by Klebsiella pneumoniae in immunocompromised patients: a retrospective cohort study - Liu, Yahui; Huang, Lin; Cai, Jing; Zhu, Haixing; Li, Junjie; Yu, Youchao; Xu, Yumin; Shi, Guochao; Feng, Yun (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose: With advancements in medical technology and the growth of an aging society, the number of immunocompromised patients has increased progressively. Klebsiella pneumoniae (K. pneumoniae) is one of the most common opportunistic pathogens, causing a severe disease burden. We aimed to further clarify the differences in respiratory tract K. pneumoniae infections between immunocompromised and immunocompetent populations. Methods: We retrospectively compared cases of respiratory tract K. pneumoniae infection in immunocompromised and immunocompetent patients admitted to Ruijin Hospital in Shanghai between January 2019 and August 2020 to clarify the differences between the two groups. Results: We enrolled 400 immunocompromised patients and 386 immunocompetent patients. Compared to the immunocompetent group, immunocompromised patients were more likely to develop bacteremia and shock and to require mechanical ventilation support during hospitalization. Immunocompromised patients also had a greater probability of polymicrobial infection and a higher rate of antibacterial resistance to carbapenem, which resulted in a higher intensive care unit admission rate, 30-day case fatality rate (CFR), and 6-month CFR. Multivariate analysis indicated that immunocompromised patients with respiratory diseases (odds ratio [OR], 2.189; 95% confidence interval [CI], 1.103-4.344; P = 0.025) and cardiovascular diseases (OR, 2.008; 95% CI, 1.055-3.822; P = 0.034), using mechanical ventilation (OR, 3.982; 95% CI, 2.053-7.722; P = 0.000), or infected with multidrug-resistant K. pneumoniae (OR, 3.870; 95%, 1.577-9.498; P = 0.003) were more likely to have a higher 30-day CFR. Conclusions: The disease burden of K. pneumoniae infection in immunocompromised patients is high. Immunocompromised patients who presented with respiratory diseases and cardiovascular diseases, used mechanical ventilation, or were infected with multidrug-resistant K. pneumoniae experienced a higher 30-day mortality rate.